Enseignement de l'architecture et marche du travail - Verges-Escuin, Ricardo (Canadian Journal of Higher Education, 1977)
This study has been carried out on three levels. Firstly, the precise definition of an instru-ment for measurement of the supply and demand of architects. Following this, the appli-cation of the measurement to the specific case of Quebec in such a way as to clearly pose the questions concerning the economic integration of the profession. Finally, a forecast of the variables that explain the demand with a view to their integration into a system of educational planning. In particular, forecasting of real estate investment are derived from the probable evolution of available real estate broken down according to population, revenue and consumer preference. This last section makes the study of interest to those in all economic disciplines and activities concerned with real estate construction and building sites.